Arahan Struktur Tata Ruang Kawasan Agropolitan Kecamatan Baros Kabupaten Serang Provinsi Banten - D. Ma’mun; T. Karyani; N Syamsiyah (Faculty of Agriculture, Pattimura University, 2013)
Baros is a district in Serang, Banten sub-district namely Baros. Sub-districts Baros has elevations between 112 m to 276 m above sea level (dpl), having a topographical 58 % flat and 42 % sloping. Soil texture was dominated by the texture of sandy loam and high porosity. The formation of regional agropolytant conformity land was based on analysis conducted by Bogor Agriculture Institute of land suitability in sub-district Baros for horticulture and food crops. Agopolytant are hoped to make synergy of the local potentials with the external potentials to be much more effecient. This research were conducted mainly to show that: 1) to identify economy activities to be developed in sub-district baros, 2) To give directions and desicision on the structure of the area for development of agropolytant in the Baros region. The method used were descriptive surveys with unit analysis on the subdistrict of Baros and the regency of Serang in Banten province. Results from the research showed the economy activities that could be more developed in the Baros subdistrict for developing agropolytant region through division of district such as: 1) Baros village would be the main farming spot. 2) Panyirapan and Sindangmandi village would be the back up or an assist for water resources, and 3) Sinarmukti, Sidawangi, Padasuka, Sukamanah, Sukaindah, Sukamenak, Cisalam, Curug agung, Tamansari, and Sukacai village would be the service as centres of the rice and horticulture production and developing agroforesty through intergrated farming